2019
DOI: 10.1186/s13148-019-0643-z
|View full text |Cite
|
Sign up to set email alerts
|

Increased methylation upstream of the MEG3 promotor is observed in acute myeloid leukemia patients with better overall survival

Abstract: BackgroundThe delta-like non-canonical Notch ligand 1 (DLK1)-maternally expressed 3(MEG3) locus (DLK1-MEG3 locus) plays a critical role in the maintenance and differentiation of hematopoietic stem cells. Accumulating evidence implicates the imprinted genes from this locus, DLK1 and MEG3, in the development and progression of acute myeloid leukemia (AML). However, the contribution of this locus to the treatment response of patients and their survival is unknown.MethodsDNA methylation of select CG dinucleotide-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…MEG3 is significantly downregulated in AML patients’ tissue samples and cell lines when compared to normal controls, particularly in the Wilms’ tumor 1 (WT1) or ten–eleven translocation 2 (TET2) mutant AML patients [92,345,346]. DNA hypermethylation of CpG sites within the MEG3 promotor region can be seen in bone marrow (BM) samples from AML patients, and decreased TET2 expression level in AML patients may result in elevated MEG3 promoter methylation, which ultimately represses MEG3 expression and causes AML development [346,347]. Additionally, overexpression of MEG3 in MOLM-13 cell line inhibits cell proliferation and induces apoptosis and G0/G1 cell cycle arrest when compared with controls [345].…”
Section: Lncrnas In Hematological Malignanciesmentioning
confidence: 99%
“…MEG3 is significantly downregulated in AML patients’ tissue samples and cell lines when compared to normal controls, particularly in the Wilms’ tumor 1 (WT1) or ten–eleven translocation 2 (TET2) mutant AML patients [92,345,346]. DNA hypermethylation of CpG sites within the MEG3 promotor region can be seen in bone marrow (BM) samples from AML patients, and decreased TET2 expression level in AML patients may result in elevated MEG3 promoter methylation, which ultimately represses MEG3 expression and causes AML development [346,347]. Additionally, overexpression of MEG3 in MOLM-13 cell line inhibits cell proliferation and induces apoptosis and G0/G1 cell cycle arrest when compared with controls [345].…”
Section: Lncrnas In Hematological Malignanciesmentioning
confidence: 99%
“…It thus implies that DNA methylation may serve as an additional parameter in the stratification of AML patients. At a glance, many studies have already investigated the clinical implications of DNA methylation in AML (Table 1) [18,21,83,84,85,86,87,88,89,90,91,92,93,94]. In this section, we discuss the potential of DNA methylation assessment in AML diagnosis and prognosis, and in the evaluation of therapeutic efficacy.…”
Section: Clinical Implications Of Dna Methylation In Amlmentioning
confidence: 99%
“…Over time, several research groups have shown different prognostic capabilities of expression and methylation profiling [6][7][8]. Nonetheless, most molecular biology markers used in clinical practice are represented by gene mutations, while DNA methylation and RNA expression are commonly only used within the research setting [6,[9][10][11][12]. This might be due to economic reasons, levels of evidence, and the reproducibility that can be achieved.…”
Section: Introductionmentioning
confidence: 99%